ANALISIS PENERAPAN PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM(PK-BLU) POLITEKNIK KESEHATAN KEMENKES BENGKULU - Riyadi, Agung (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
fter two years of implementing the financial management of BLU, there is still themanager of the department / study program who do not understand the flexibility of financialmanagement that offers efficiency and productivity, have not seen the role of the supervisoryboard (a god) to the financial coaching BLU. Value turnover was still below the minimumrequirement, Operational Cooperation is still very minimal, opinions BLU is still small (under15 billion) and the remuneration of the BLU can not be granted to managers and employeesBLU officials. The purpose of this study was to determine the application overview ManagedHealth Polytechnic BLU MoH Bengkulu. This research was conducted with qualitative. Theunit of analysis of research data is Poltekkes MoH Bengkulu. The subject of research is theDirector, Pudir, Kasubbag Adum, Kaur Finance, kaur and Staff Officer, Treasurer BLU,Treasurer non-tax revenues, financial reporting staff, Ka. Planning Unit, Kajur/Sekjur,department managers, lecturers and students of each department / study program. Thesampling technique purposive sampling, namely the determination of the sample based oncertain criteria and based on the consideration of researchers. The results showed that 1) Theperception of the BLU is different - different. 2) Budget planning is already using the RBA asthe budget plan. 3) Source BLU reception from the state budget in the form of pure Rupiahand non-tax revenues came from students and other funding sources. 4) Has had threeaccounts that have been approved by theMinistry of finance. 5) The financial statements BLUconsist of the balance sheet, budget realization reports, activity reports, cash flow statementand notes to the financial statements and there are no clear technical guidelines on financialreporting BLU. 6) Have been prepared BLU performance accountability report. 7) Neverbefore have a budget deficit, and is still running a budget surplus. 8) Dewas still held byofficials not yet fully substitute god that can run all functions of a god .. 9) Monitoring offinancial management BLU implemented by SPI, Itjend, and the Office of PublicAccountants. 10) The remuneration system BLU yet fully implemented, the implementationof remun still follow the pattern of the ministries / agencies.